2019
DOI: 10.2139/ssrn.3472856
|View full text |Cite
|
Sign up to set email alerts
|

Domestic and Foreign Investment in Advanced Economies. The Role of Industry Integration

Abstract: The Working Paper Series seeks to disseminate original research in economics and finance. All papers have been anonymously refereed. By publishing these papers, the Banco de España aims to contribute to economic analysis and, in particular, to knowledge of the Spanish economy and its international environment. The opinions and analyses in the Working Paper Series are the responsibility of the authors and, therefore, do not necessarily coincide with those of the Banco de España or the Eurosystem. The Banco de E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 4 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…Similarly, Abdouli and Hammami (2020) suggest that financial and economic policies should focus on protecting the environment along with economic growth, with a better level of financial development and FDI inflow. Sastre and Recuero (2019) suggested that the relationship between domestic investment and FDI depends on the type of industry and has a high forward integration with the global value chain. According to Faeth (2006) FDI, economic growth and domestic investment directly influence each other; however, they indirectly influence the trade variables.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Abdouli and Hammami (2020) suggest that financial and economic policies should focus on protecting the environment along with economic growth, with a better level of financial development and FDI inflow. Sastre and Recuero (2019) suggested that the relationship between domestic investment and FDI depends on the type of industry and has a high forward integration with the global value chain. According to Faeth (2006) FDI, economic growth and domestic investment directly influence each other; however, they indirectly influence the trade variables.…”
Section: Resultsmentioning
confidence: 99%